Empowering Islamic Boarding School Students Through Self-Defense Training for Personal and Spiritual Resilience - Fajli Aijat Mau; Muhammad Riski Aditia; Kevin Dimitar; Luki Saputro (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
This community service program was carried out to enhance the physical, emotional, and spiritual resilience of students (santri) at Pesantren Assyifa through integrated self-defense training. Recognizing the increasing psychological and social challenges faced by adolescents in pesantren, this program combined martial arts education with Islamic character development. Over the course of eight weeks, 36 santri participated in bi-weekly training sessions that included basic self-defense techniques, leadership drills, and reflective discussions on prophetic values such as patience (ṣabr), courage, and self-control. The program successfully improved student discipline, confidence, and peer cooperation, as measured through pre- and post-assessments and observational rubrics. Participants reported greater self-awareness and felt more empowered to respond to threats both physically and ethically. The pesantren administration expressed strong interest in continuing the initiative as part of the formal extracurricular curriculum. This activity not only strengthened the personal capabilities of santri but also aligned with the broader goal of fostering holistic Islamic education that nurtures the body, mind, and soul. The combination of physical practice and moral reflection proved to be a sustainable and transformative approach to santri empowerment.